Pemetaan Genom фAfaNA-1 Sebagai Agen Terapi Infeksi Bakteri Patogen Ulkus Diabetes - Dhiva Aulia Winda Utami (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Bacteriophages are a good therapeutic alternative to overcome bacterial infections, especially in the case of diabetic ulcers that are difficult to treat due to antibiotic resistance. This study focuses on mapping the φAfa-NA1 genome to identify functional genes that play a role in the life cycle of bacteriophages and their potential as therapeutic agents, using a bioinformatics approach based on Open Reading Frame (ORF) analysis. The genome analysis of φAfa-NA1 revealed 83 potential ORFs, showing similarities in gene arrangement with the T7, CASP1, and vB AfaP QDWS595 bacteriophages. Key findings include the identification of orf-7 encoding RNA polymerase, orf-16 encoding ligase, orf-29 encoding DNA polymerase, orf-42 encoding capsid protein, and orf-79 encoding lysozyme. These results provide valuable insights into the adaptation and evolutionary mechanisms of bacteriophages and affirm the therapeutic potential of φAfa-NA1 as an effective agent against antibiotic-resistant pathogenic bacteria in diabetic ulcer patients. This research establishes a foundation for the development of bacteriophage-based phagotherapy, offering an innovative, specific, and effective alternative for managing chronic infections
Reaploud Repository February 2026 Hasyim
Keywords: Bacteriophage; diabetic ulcer; open reading orame (ORF